Elevation Salivary C - Reactive Protein (CRP) Levels in Iraqi Women with Polycystic ovary syndrome (PCOS ) and Oral diseases (Mustansiria Dental Journal, 2018)
Background: Polycystic ovary syndrome (PCOS) is the most commonendocraniopathy in women of reproductive age, affecting (5-10) % of populationand it is the leading cause of female infertility.C-reactive protein CRP, is a member of a group of acute phase of protein whichincrease their concentrations during certain inflammation disorders and used as abiomarker of inflammation in the body.Aim of the study: is to assess the salivary level of CRP with were oral disease wasstimulated by evaluate gingival inflammation, plaque accumulation in some Iraqiwomen with PCOS disease in compared with women not have PCOS.Methods: 19 females with PCOS and 26 females with systemically healthy include inthis study. Saliva were collected and CRP were examined and evaluated by usingELISA method in both study and control group. For all groups we examine theoral inflammation was measured depending on gingival and plaque index.Results: the results reported all PCOS women have significant increase in the salivaryCRP than women with no PCOS) mean ± SD (226.8±34SD, 173.8±22.5respectively). All women with PCOS had significantly increased in gingivitis thanwith no PCOS women.Conclusion:An increase in salivary CRP and gingival inflammation were found in womenwith PCOS. Also suggested measurement of salivary CRP may be helpful inpredicting women with oral disease in PCOS women.